Development of the Flappy Helicopter Game Using Scratch - Eldo, Handry; Naurah, Rizky Indah (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
The development of the Fruit Ninja game using Scratch is an innovative and educational project. By utilizing Scratch, this game development allows users to express their creativity in designing fruit characters, sound effects, and unique game mechanics. This process also provides a deep understanding of basic programming concepts such as logic, loops, branching, and variables, presented in an intuitive and easy-to-understand interface. Additionally, this game development involves in-depth analysis in designing game flow, score management, and difficulty levels, which can enhance users' analytical skills. Through the Scratch platform, users also have the opportunity to collaborate and share projects with the online community, receive feedback, and improve their skills. With a step-by-step approach, users can start with basic features and gradually add additional features to create a fun and educational game. This project combines creativity, programming learning, and community interaction to produce a beneficial and educational product.